Effect of anserine-containing fish-sausage supplementation on high-intensity exercise - Kato, S.; Ogata, H.; Tsukahara, H.; Aoshima, Y.; Kobayashi, Y.; Muneda, H.; Shiina, Y.; Omi, N. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: A large amount of the histidine-containing dipeptide carnosine and anserine has been to be present within the skeletal muscle of most vertebrate species. It has been reported (1) that carnosine and anserine are effect of blood lactate buffering, remove of reactive oxygen species and reduction of muscle fatigue. Maemura (2) was reported carnosine concentration in skeletal muscle increase by carnosine and anserine high-containing drink supplementation. And also performance of high-intensity intermittent exercise was improved by the carnosine and anserine high-containing drink supplementation. Anserine is can´t be existence in human skeletal muscle (3), however, anserine and those constitution amino acids was temporary detected in blood by carnosine or/and anserine supplementation (2). The purpose of this study was to examine the effects of anserine-containing fish-sausage supplementation after exhaustion exercise on high-intensity exercise performance. Methods: Twenty four male students (body weight: 67.7±9.48kg) as subjects in the present study. The subjects randomly selected and divided into three groups (High-anserine, Low-anserine, 0-anserine). Subjects was performed drop-jump and 30-s maximal sprinting exercise for exhaustion exercise. Two hours after completing the exhaustion exercise, the subjects performed the high-intensity intermittent exercise (EX). Intermittent exercise consisted of ten 5-s maximal sprints with 25-s of recovery between each sprint. Also, subjects was took the test sample for fish-sausage (20g) after the exhaustion exercise during 10-15 minutes. Fish-sausage anserine-containing quantity was determined according to previous study (4), each at High-group 400mg, Lowgroup 50mg, 0-group 0mg. Mean power was measured each sprint for an assessment of the EX performance. The data was expressed division by subject weight. Results: In the mean power, it was not statistically significant, but it was suggested that possibility have a tendency to keep anserine concentration-dependent in the final set.